Applications of microscopy and small angle scattering techniques for the characterisation of supramolecular gels - MacDonald, Connor R. M.; Draper, Emily R. (Beilstein Journal of Organic Chemistry, 2024)
When evaluating soft self-assembling materials for use in any application, the structural or morphological characterisation is highly important. We know that the hierarchal molecular self-assembly of these materials into larger structures directly influences behaviours such as performance and stability. It is therefore imperative that these materials are characterised effectively over multiple length scales. Two effective methods of achieving this are small angle scattering (SAS) and imaging. Scattering giving us indirect information about the systems, whereas imaging is often looking at the material directly. In this review, we discuss the benefits, caveats and power of using both these techniques separately and together for the characterisation of supramolecular gels.
Keywords: characterisation; electron microscopy; gelators; small angle scattering; supramolecular materials